2009
DOI: 10.3174/ajnr.a1575
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain in Temporomandibular Joint Disorders: Case-Control Analysis by MR Imaging

Abstract: BACKGROUND AND PURPOSE: Temporomandibular joint disorders (TMJ-D) may be associated with the onset of neuropathic pain. The purpose of this study was to prospectively assess if, at the open-mouth position, the distance between the temporomandibular joint (TMJ) disk and the mandibular nerve is shorter in patients with TMJ-D and neuropathic pain vs patients with TMJ-D without neuropathic pain or in healthy people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…These differences may be due to the different methodologies used in the studies where the diagnostic method and causes of OFP considered were different, which makes comparisons difficult. Pedullà et al 22 think that TMD and NP can be related. Using imaging methods, they found that in patients with TMD and NP, the distance between the articular disc and the mandibular nerve was lower than in patients with TMD without NP.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be due to the different methodologies used in the studies where the diagnostic method and causes of OFP considered were different, which makes comparisons difficult. Pedullà et al 22 think that TMD and NP can be related. Using imaging methods, they found that in patients with TMD and NP, the distance between the articular disc and the mandibular nerve was lower than in patients with TMD without NP.…”
Section: Discussionmentioning
confidence: 99%
“…In the orofacial, TMJ, and masticatory muscle regions, pain symptoms originate from various factors including musculoskeletal, vascular, neurovascular, neuropathic, psychogenic, and infectious diseases [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…TMDs may be associated with the onset of neuropathic pain [158] . Although TMJ pain seems to correlate with the presence of internal derangement, joint effusion, OA, and bone marrow edema within the TMJ, the possible causes of neuropathic pain in patients with TMDs are less clear [3] , [28] , [53] .…”
Section: Tumor Involvement Inflammatory Process and Autoimmune Diseamentioning
confidence: 99%